2020
DOI: 10.3389/fneur.2020.00098
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Behavioral and Genetic Outcomes Associated With Administration of TA65 (A Telomerase Activator) Following Repetitive Traumatic Brain Injury: A Pilot Study

Abstract: Children and adolescents have the highest rates of traumatic brain injury (TBI), with mild TBI (mTBI) accounting for most of these injuries. This demographic also often suffers from post-injury symptomologies that may persist for months. Telomere length (TL) has previously been used as a marker for outcomes following repetitive mild TBI (RmTBI) and it may be possible that telomere elongation can reduce post-traumatic behavioral impairments. Telomerase activator-65 (TA-65) is a telomerase small-molecule activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Mice fed TA-65 -and not the control -exhibited significant alterations in the subcutaneous fat layer and more proliferation of epidermis [3]. Also, female Sprague-Dawley rats increased mRNA levels of TERT and telomerase associated protein (Tep1) in the cerebral prefrontal cortex and hippocampus after oral supplementation with TA-65 following repetitive traumatic brain injury; unsupplemented controls showed no increase [59]. Another demonstration of tissue distribution of TA-65 after oral supplementation was shown in a transgenic mouse model of Parkinson's disease [40]: Oral TA-65 increased TERT protein in the brain neocortex and hippocampus, resulting in decreased -synuclein protein levels and improvement of motor functions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mice fed TA-65 -and not the control -exhibited significant alterations in the subcutaneous fat layer and more proliferation of epidermis [3]. Also, female Sprague-Dawley rats increased mRNA levels of TERT and telomerase associated protein (Tep1) in the cerebral prefrontal cortex and hippocampus after oral supplementation with TA-65 following repetitive traumatic brain injury; unsupplemented controls showed no increase [59]. Another demonstration of tissue distribution of TA-65 after oral supplementation was shown in a transgenic mouse model of Parkinson's disease [40]: Oral TA-65 increased TERT protein in the brain neocortex and hippocampus, resulting in decreased -synuclein protein levels and improvement of motor functions.…”
Section: Discussionmentioning
confidence: 98%
“…This is indeed encouraging because a possible adverse effect of dietary telomerase might have been the enhancement of tumorigenesis. In fact, many researchers (who have themselves demonstrated the efficacy of TA-65 in slowing age-related diseases and cellular senescence and possibly even mortality) realize the importance of ensuring "that administration of a telomerase activator does not increase susceptibility to / or risk for cancer or cancer related diseases" [59]. Because skin cancer is by far the most common human cancer, the absence of any change in the magnitude of skin cancer incidence with oral TA-65 attests to the safety of this supplement.…”
Section: Discussionmentioning
confidence: 99%
“…The small molecule Telomerase activator-65 (TA-65, also known as cycloastragenol) is derived from various legume species in the genus Astragalus and is a potent telomerase activator that can lengthen telomeres. Treatment with TA-65 improved motor coordination and reduced depressive-like behaviour in female, but not male, rats that sustained repeated mTBI, and increased mRNA expression of telomere-length related genes telomerase reverse transcriptase (TERT) and telomerase-associated protein-1 (Tep1) (Eyolfson et al, 2020). Further studies should be conducted to establish links between the prognostic outcomes of TBIs, cellular aging, telomere length and NAM/vitamin B3 as a putative therapy for TBI-induced pathologies.…”
Section: Vitamin B3 (Nicotinamide)mentioning
confidence: 99%
“…These results are similar to those described by Eyolfson and co-authors who treated rats for one month with TA-65 before inflicting a brain injury. The authors found an increase in Tert expression as well as an improvement in motor coordination in the treated rats compared to controls [ 68 ].…”
Section: Increasing Telomerase/tert Levels In Ageing Brain and As Thementioning
confidence: 99%